Direct PCR for Escherichia coli: a straightforward and cost-effective method - Harahap, Desy Aryani; Yamamoto, Zulham; Widjaja, Sry Suryani; Mayasari, Evita (JURNAL KESMAS DAN GIZI (JKG), 2025)
This study compares the direct PCR method with standard PCR to detect Escherichia coli. Escherichia coli is the most widely used organism in biology. Detection of E. coli in water and food is routinely performed, utilizing methods like PCR. The initial stage of PCR preparation involves DNA extraction, which requires a commercial kit. Consequently, this extraction process incurs additional expenses, time, and labor. Therefore, an alternative method is needed, such as direct PCR, which can circumvent the need for DNA extraction. The PCR process facilitates lysis of the bacterial cell wall, releasing nucleic acids, which can then be amplified by Taq polymerase. For the PCR procedure, two groups were formed, each comprising three replicates of the reaction with different DNA templates. The first group utilized a direct culture of Escherichia coli, while the second group incorporated the extracted DNA of Escherichia coli. Our study successfully amplified the metH gene of Escherichia coli without DNA extraction. Electrophoresis analysis revealed that the direct PCR product, sized at 300 bp, appeared more pronounced than the standard PCR product. The findings of this research demonstrated direct PCR as an alternative for detecting Escherichia coli, which would lead to reductions in costs, time, and labor.